Factors Associated with Employment Status and Sex Differences in Occupational Continuity among Cancer Survivors: A Cross-Sectional Study Using the Korea National Health and Nutrition Examination Survey - Bomi Hong; Seong Kwang Kim; Suk Jae Park (Korean Journal of Adult Nursing, 2026)
Purpose: This study examined sociodemographic, clinical, and symptom-related factors associated with current employment among cancer survivors and described sex-based differences in occupational continuity. Methods: This cross-sectional study used data from the 2019 and 2021 Korea National Health and Nutrition Examination Survey. The sample included cancer survivors aged 19 to 65 years who did not have multiple primary cancers or missing data (n=289). Employment status was categorized as employed or non-employed. Sociodemographic factors (age, sex, education, marital and household characteristics, household income, and private insurance), clinical factors (time since diagnosis, cancer type, current cancer status, and comorbidity), and symptom-related factors (pain, fatigue, depression, memory problems, and sleep difficulties) were evaluated using hierarchical logistic regression. Weighted descriptive analyses were performed to examine sex-based differences in occupational continuity.Results: Overall, 56.6% of participants were employed. In the final model, male sex was associated with higher odds of employment (odds ratio [OR], 4.69; 95% confidence interval [CI], 2.21–9.94; p